2022
DOI: 10.3390/cancers14051359
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps in Cancer Therapy Resistance

Abstract: Neutrophils and their products are increasingly recognized to have a key influence on cancer progression and response to therapy. Their involvement has been shown in nearly every aspect of cancer pathophysiology with growing evidence now supporting their role in resistance to a variety of cancer therapies. Recently, the role of neutrophils in cancer progression and therapy resistance has been further complicated with the discovery of neutrophil extracellular traps (NETs). NETs are web-like structures of chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 153 publications
(293 reference statements)
1
37
0
1
Order By: Relevance
“…Given that NETs can also bind systemically administered DOX in circulating blood, NETs in serum may significantly impair the pharmacokinetics of systemically administrated drugs. Indeed, recent studies have suggested the possibility that NETs may have a role in resistance to chemo-, immuno- or radiotherapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that NETs can also bind systemically administered DOX in circulating blood, NETs in serum may significantly impair the pharmacokinetics of systemically administrated drugs. Indeed, recent studies have suggested the possibility that NETs may have a role in resistance to chemo-, immuno- or radiotherapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…PH4B is also linked to chemoresistance [ 29 31 ]. Emerging evidence indicates that neutrophil NETosis is a central contributor to cancer proliferation and chemoresistance [ 32 ]. Overall, the identified candidate genes may serve as molecular mechanisms underlying F. nucleatum neutrophil-stimulated NETosis with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying immune checkpoint blockade resistance are poorly understood and have been the subjects of intense scrutiny in recent years. In several recent studies, NETs have been examined as novel mediators in some tumors that resist checkpoint inhibition (14)(15)(16)(17)(18). Using a PDAC model, Zhang et al demonstrated that IL17 triggered the formation of NETs within tumors, which can lead to the exhaustion of cytotoxic CD8+ T cells in tumors.…”
Section: Nets In Immunotherapy Resistancementioning
confidence: 99%
“…In addition to the roles they play in host defense, NETs have been widely implicated in noninfectious diseases, such as autoimmune diseases (2)(3)(4), rheumatic diseases (5,6), thrombosis (7)(8)(9), diabetes (10), and atherosclerosis (11-13). Increasing evidence indicates that NETs play a critical role in the TME, including in tumor progression, metastasis and therapy resistance (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The effects of NET-related components seem to be intertwined and complicated.…”
Section: Introductionmentioning
confidence: 99%